2012
DOI: 10.1074/jbc.m112.394338
|View full text |Cite
|
Sign up to set email alerts
|

The E3 Ubiquitin Ligase HOS1 Regulates Arabidopsis Flowering by Mediating CONSTANS Degradation Under Cold Stress

Abstract: Background: Intermittent cold stress delays flowering. This results from interaction between the cold and photoperiodic pathways. Results: CO protein is degraded through an HOS1-mediated ubiquitination mechanism during brief cold treatments. Conclusion: CO acts as a molecular hub that integrates photoperiod and cold signals into the flowering genetic pathways. Significance: The CO-HOS1 module is crucial for fine-tuning of photoperiodic flowering under short term temperature fluctuations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
104
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 52 publications
0
104
0
1
Order By: Relevance
“…The early flowering phenotype of hos1 mutants is due to the precocious upregulation of FT expression levels and is completely suppressed by mutations in the CO gene in the Landsberg erecta (Ler) background (Lazaro et al, 2012). Moreover, we showed that HOS1 physically interacts with CO in Arabidopsis and that the CO protein abnormally accumulates in the hos1 mutant during the early hours of the daylight period (Jung et al, 2012;Lazaro et al, 2012). Altogether, these observations suggest that a complex regulatory mechanism ensures that CO accumulates only at the end of a LD, allowing a correct seasonal response.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…The early flowering phenotype of hos1 mutants is due to the precocious upregulation of FT expression levels and is completely suppressed by mutations in the CO gene in the Landsberg erecta (Ler) background (Lazaro et al, 2012). Moreover, we showed that HOS1 physically interacts with CO in Arabidopsis and that the CO protein abnormally accumulates in the hos1 mutant during the early hours of the daylight period (Jung et al, 2012;Lazaro et al, 2012). Altogether, these observations suggest that a complex regulatory mechanism ensures that CO accumulates only at the end of a LD, allowing a correct seasonal response.…”
Section: Introductionmentioning
confidence: 83%
“…Previous results showed that HOS1 and CO proteins physically interact in planta (Jung et al, 2012;Lazaro et al, 2012). To explore the possibility of a direct interaction between phyB and HOS1 or CO, we expressed the C-terminal part of HOS1 (cHOS1), the C-terminal part of phyB (cPHYB), and full-length CO and COP1 in yeast cells to perform two-hybrid experiments (Yu et al, 2008).…”
Section: Hos1 Co and Phyb Proteins Interact In Plantamentioning
confidence: 99%
See 3 more Smart Citations